Combined hepatocellular‐cholangiocarcinoma in a patient with Abernethy malformation and tetralogy of Fallot: A case report. Issue 5 (24th June 2016) - Happaerts, Sofie; Foucault, Amélie; Billiard, Jean Sébastien; Nguyen, Bich; Vandenbroucke‐Menu, Franck
Abstract : Abernethy malformation is a rare congenital anomaly of the portal vein where the portal blood bypasses the liver. We report the first case of a patient with Abernethy malformation and tetralogy of Fallot associated with nodular regenerative hyperplasia and focal nodular hyperplasia (FNH), which finally evolved to a giant hepatocellular‐cholangiocarcinoma (HCC‐CC) of the liver, successfully resected. (Hepatology 2016;64:1800‐1802)